2023
DOI: 10.7759/cureus.43743
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Insulin Autoimmune Syndrome in an Indian Male Taking Alpha-Lipoic Acid

Tanisha Sehgal,
Uday Ohri,
Naveen Mittal
et al.

Abstract: Insulin autoimmune syndrome [IAS, Hirata disease (HD)] is a rare cause of recurrent spontaneous hypoglycemic episodes, characterized by high serum insulin levels and high titers of autoantibodies against endogenous insulin. We report a case of a previously healthy Indian male presenting with recurrent episodes of hypoglycemia with no prior exposure to exogenous insulin. Regular glucose monitoring was done. Laboratory tests showed insulin >1000 μIU/mL and C-peptide levels of 12.8 ng/ml. The patient had high tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was estimated that drug-induced AIS accounted for about 50% of the total in the Caucasian population. AIS has a high strength of association with anti-thyroid drugs and alpha lipoic acid, while other drugs have a low strength of association (less than five case reports) [ 11 ]; notably, in a recent study, a case report was reported with AIS in a male patient taking alpha-lipoic acid [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that drug-induced AIS accounted for about 50% of the total in the Caucasian population. AIS has a high strength of association with anti-thyroid drugs and alpha lipoic acid, while other drugs have a low strength of association (less than five case reports) [ 11 ]; notably, in a recent study, a case report was reported with AIS in a male patient taking alpha-lipoic acid [ 12 ].…”
Section: Discussionmentioning
confidence: 99%